2008
DOI: 10.1159/000184696
|View full text |Cite
|
Sign up to set email alerts
|

Benign copy number changes in clinical cytogenetic diagnostics by array CGH

Abstract: A database of apparently benign copy number variants (bCNVs) detected by a Spectral Genomics Inc./PerkinElmer BAC array platform has been maintained through the University of Utah Comparative Genomic Hybridization laboratory since 2005. The target population for this database represents 1,275 patients with abnormal phenotypes, primarily children referred for developmental delay and mental retardation. These bCNVs are independent of any identified copy number abnormality detected. The most common 35 bCNVs obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…These seven were ascertained with congenital anomalies, autism, secondary amenorrhoea, infertility, miscarriages and a family history of intellectual difficulties and cystic fibrosis (Table 2). However, this EV is unlikely to be a cause of congenital anomalies or autism because: (1) there was no consistency in the indications in Patients 2, 3 and 4, and the congenital anomalies in Patient 4 were most likely explained by her trisomy 9 mosaicism; (2) the three patients referred for reproductive reasons were otherwise normal (Patient 1; Manvelyan et al, 9 Patients 1 and 2); (3) the 12-kb VNTR repeat array contains only the REXO1L1 gene cluster that has no known pathology to date; (4) the variant region overlaps RP11-96G1 which is a common benign CNV 34 and corresponds with locus 4603a in the Database of Genome Variants (DGVs). 35 A possible association with infertility and/or miscarriage 9 would need testing in much larger cohorts and is more likely to reflect bias of ascertainment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These seven were ascertained with congenital anomalies, autism, secondary amenorrhoea, infertility, miscarriages and a family history of intellectual difficulties and cystic fibrosis (Table 2). However, this EV is unlikely to be a cause of congenital anomalies or autism because: (1) there was no consistency in the indications in Patients 2, 3 and 4, and the congenital anomalies in Patient 4 were most likely explained by her trisomy 9 mosaicism; (2) the three patients referred for reproductive reasons were otherwise normal (Patient 1; Manvelyan et al, 9 Patients 1 and 2); (3) the 12-kb VNTR repeat array contains only the REXO1L1 gene cluster that has no known pathology to date; (4) the variant region overlaps RP11-96G1 which is a common benign CNV 34 and corresponds with locus 4603a in the Database of Genome Variants (DGVs). 35 A possible association with infertility and/or miscarriage 9 would need testing in much larger cohorts and is more likely to reflect bias of ascertainment.…”
Section: Discussionmentioning
confidence: 99%
“…This frequency could be an underestimate as this EV is usually discernible only in high quality chromosome preparations of at least 550 band level resolution and may have gone undetected in lower resolution chromosomes or where band 8q21.2 is unclear. In addition, Whitby et al 34 found CNVs of RP11-96G1 in 142/1275 (1 in 9) clinically affected patients, which suggests that B1% (9/770) of these CNVs may be microscopically visible. The DGV also indicates that the background frequency of CNVs across the 8q21.2 EV region is high with gains and losses found in 10/49 patients and controls 35 and 9/90 Yoruban individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Enh signals from non-contiguous BACs RP11-410P5 and RP11-80F22 (Table 1) were thought to be independent variation especially as RP11-80F22 is one of the commonest CNVs found using diagnostic oaCGH. 24 The formal karyotype was: 46,XY,var(16) (p11.2p11.2). ish var (16) …”
Section: Patientmentioning
confidence: 99%
“…3 D'Apice et al 2 used loss of hybridisation signal from a single bacterial artificial chromosome (BAC) to imply that the whole REXO1L1 cluster had been deleted but their BAC (RP11-96G1) only partially overlaps this region (Supplementary Figure 1) and residual copies of the 12 kb repeat might not have been detected using FISH. BAC RP11-96G1 is also one of the commonest benign CNVs found using BAC aCGH 4 and subject to loss, gain and inversion in the database of genomic variants.…”
Section: Microdeletion or Euchromatic Deletion Variant?mentioning
confidence: 99%